(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2021)
In this article, I analyze one of the most interesting confessional works, Religio medici, by Thomas Browne (1642), English physician and thinker. This treatise, written in labyrinthine prose, full of apparent contradictions and paradoxes, is interesting not only as a literary work but also as a philosophical one. I discuss its content in the context of seventeenth-century England’s religious and intellectual changes (doctrinal disputes, religious rationalization, the emergence of a new paradigm in the philosophy of nature). The existential interpretation of Religio medici presented in the article shows the coherence of the treatise and reveals the essence of Browne’s religious attitude.